Arthropod Community Structure in Oil Palm Nurseries: Struktur Komunitas Artropoda di Pembibitan Kelapa Sawit - Siska Efendi; Puji Setiawati; Yaherwandi (CELEBES Agricultural, 2023)
Nurseries are one of the essential agronomic activities in oil palm cultivation. Oil palm seedlings are cultivated on a large scale, different from nurseries for other plantation commodities. The nursery expanse comprises various biotic components, one of which is Arthropods. This study aims to determine the Artropod community and its function in oil palm nurseries. The research was carried out at two nurseries, Nagari Gunung Medan and Nagari Kurnia Selatan, Dharmasraya Regency, West Sumatra Province. Sampling using the pitfall trap, yellow pan trap, insect nets, and direct collection methods. The results showed that the Arthropods that make up the oil palm nursery ecosystem were insects and spiders. Arthropods in oil palm nurseries act as phytophages, predators, parasitoids, and detrivores. Phytophage insects found in oil palm nurseries were 700 individuals consisting of 4 orders, nine families, and 14 genera/species. Predatory insects, parasitoids, and detritivores were found in as many as 466 individuals consisting of 5 orders, 14 families, and 16 genera/species. There are two species of spiders in oil palm nurseries: Pardosa sp and Oxyopes javanus. Valanga sp was the species with the highest number of individuals in oil palm nurseries.